The deregulation of professional services: A marketing challenge - Hélène Brice; B. Phillips (South African Journal of Business Management, 1986)
Professional services are undergoing a process of self-examination in respect of deregulation of certain areas of conduct. This has been the response to competitive pressures on the professional services, and to developments in other countries. As a result, the marketing area has been put to the fore in the various professions. The authors seek to provide a conceptual framework within which the practitioner in professional service can consider the trend towards a marketing orientation, and propose some profitable directions for action and further research.
Keywords: 650